Optimalisasi Proses Produksi di Balerina Fashion melalui Penerapan Lean Manufacturing dengan Metode VSM dan PAM - Eko Wirawan; Fithriya Nur Hana; Bayu Febriyanto; Purwanti Purwanti; Rizky Eka Saputra; Ari Zaqi Al-Faritsy (Jurnal Sains dan Teknologi, 2024)
Balerina Fashion faces the problem of waste in production process activities, which is caused by errors in pattern cutting, repetitive activities between production stages, and double work in the Quality Control (QC) division. This study aims to improve the efficiency of the production process by reducing waste using the Lean Manufacturing approach through the Value Stream Mapping (VSM) and Process Activity Mapping (PAM) methods. The results showed a significant increase in Value Adding (VA) time, from 56.00% to 84.88%. In contrast, Non-Value Adding (NVA) time decreased dramatically from 35.74% to 3.33%, while Necessary Non-Value Adding (NNVA) time increased slightly from 8.25% to 11.79%. These changes reflect productivity improvements and an increased focus on activities that provide direct value to customers. As a recommendation, the development of a new Standard Operating Procedure (SOP) is suggested to ensure each process runs according to standard. This SOP includes a detailed step-by-step guide for operators and QC, which was previously unavailable.